PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KARTU INTERNET INDOSAT OOREDO - Retno Susanti, Yemima Oktavia Astuti, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2017)
This study aims toanalyze the significance the effect of marketing mix influence onpurchasing decisionsdetermine which variables are the most dominant influence onpurchasing decisions.The research method used survey method. The population in thisstudy were students of the faculty of Economics, Management Studies Program of SlametRiyadi University unknown number. The number of samples in this study of 100respondents, the sampling technique uses accidental sampling technique. Test instrumentusing validity and reliability test. Classic assumption test using the test: multicolinearity,autocorrelation, heteroscedasticity and normality. Data analysis techniques: multiplelinear regression, t-test, F, and the coefficient of determination.The research resultsshowedproduct has significant effect to purchasing decicions, price has significant effectto purchasing decicions, promotion has significant effect to purchasing decicion, placehas significant effect to purchasing decicions, the accuracy of the model test resultsshow that the regression model used in this study is good or goodnes of fit models, placevariable had the most dominant influence on purchasing decisions.Keywords: product, price, promotion, purchasing decisions